DETERMINANTS OF LOAN LOSS PROVISIONING BEHAVIOUR IN INDIAN COMMERCIAL BANKS - AGARWAL, ANUSHREE PRADEEPKUMAR (2016)
This study focusses on the factors affecting loan loss provisioning behaviour in Indian commercial banks. It tests the income smoothing, capital management and business cycle hypothesis for the same using the Generalized Method of Moments (GMM).In addition, it tests for relationship between cost efficiency of banks and loan loss provisioning where cost efficiency is estimated using the Stochastic Frontier Analysis.The results suggest that Indian commercial banks do not use loan loss provisioning for smoothing income or managing regulatory capital. It does find a countercyclical relation of provisioning with the business cycle. The study reveals that cost efficiency does not have a relationship with loan loss provisioning behaviour.